2016
DOI: 10.1073/pnas.1604519113
|View full text |Cite
|
Sign up to set email alerts
|

Tau accumulation induces synaptic impairment and memory deficit by calcineurin-mediated inactivation of nuclear CaMKIV/CREB signaling

Abstract: Intracellular accumulation of wild-type tau is a hallmark of sporadic Alzheimer's disease (AD), but the molecular mechanisms underlying tau-induced synapse impairment and memory deficit are poorly understood. Here we found that overexpression of human wild-type full-length tau (termed hTau) induced memory deficits with impairments of synaptic plasticity. Both in vivo and in vitro data demonstrated that hTau accumulation caused remarkable dephosphorylation of cAMP response element binding protein (CREB) in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
122
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 146 publications
(127 citation statements)
references
References 83 publications
4
122
0
1
Order By: Relevance
“…Coincidently, a remarkable anxiety was reproducibly shown in the mice with CA3 injection of htau in addition to spatial memory deficits. 46 The prefrontal cortex and amygdale have been the recognized brain regions for emotional behaviors; here, we find that hippocampal CA3, a subset with enriched GABAergic neurons, also plays an important role in anxiety behavior. As the htau was expressed in both pyramidal neurons and the GABAergic neurons, it is conceivable that htau accumulation may cause the anxiety behaviors by direct impairment to the GABAergic neurons or indirectly through affecting the synaptic connections between excitatory and the GABAergic neurons.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Coincidently, a remarkable anxiety was reproducibly shown in the mice with CA3 injection of htau in addition to spatial memory deficits. 46 The prefrontal cortex and amygdale have been the recognized brain regions for emotional behaviors; here, we find that hippocampal CA3, a subset with enriched GABAergic neurons, also plays an important role in anxiety behavior. As the htau was expressed in both pyramidal neurons and the GABAergic neurons, it is conceivable that htau accumulation may cause the anxiety behaviors by direct impairment to the GABAergic neurons or indirectly through affecting the synaptic connections between excitatory and the GABAergic neurons.…”
Section: Discussionmentioning
confidence: 58%
“…By our recent findings, 46,75 we believe that the psychiatric disturbance can reciprocally interact with the onset and/or progression of dementia and vice versa. Another most recent study shows that the relationship between dementia stage and expression of behavioral and psychological symptoms of dementia (BPSD) can be variational according to the type of dementia.…”
Section: Discussionmentioning
confidence: 82%
“…Amyloid –beta treatment reduces CREB levels and can cause it to be retained in the cytoplasm (Arvanitis et al, 2007; Pugazhenthi et al, 2011), while high BACE-1 levels reduce CREB activation (Chen et al, 2012), and CREB-mediated gene expression is aberrant in brains of Alzheimer’s patients (Satoh et al, 2009). A recent study has also shown that Tau accumulation reduces CREB activity by increasing calcineurin levels (Yin et al, 2016). Together, these results suggest that impaired, or sub-optimal CREB function in aging may make aged individuals more vulnerable to Alzheimer’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…Intracellular accumulation of tau causes mitochondrial dysfunction and mitophagy deficits by increasing mitochondrial membrane potential [26,27]. Tau accumulation also disrupts intracellular calcium signaling leading to activation of calcineurin and CREB dephosphorylation in primary neuron cultures [4]. These hypothesis-driven studies partially disclose the mechanisms underlying the toxic effects of tau.…”
Section: Introductionmentioning
confidence: 98%